Integrated adsorption-membrane filtration process for antibiotic removal from aqueous solution - Sharma, Vibhu; Vinoth Kumar, R.; Pakshirajan, Kannan; Pugazhenthi, G. (Powder technology, 2017)
This study investigated the removal of two widely used antibiotics, norfloxacin (NOR) and ofloxacin (OFL) from aqueous solution by employing a novel integrated adsorption cum membrane filtration process. The application potential of the adsorbent was investigated by evaluating the effect of different process parameters; including solution pH, initial antibiotic concentration and adsorbent dosage. Among these parameters, solution pH significantly affected the removal of antibiotics due to its strong effect on the charges of the adsorbent and the adsorbate. The removal efficiency decreased with an increase in the initial antibiotics concentration and increased with an increase in the adsorbent amount. A maximum removal of 98.7% for NOR and 94.61% for OFL was achieved with 10mg/L initial concentration and at a solution pH of 7. A high removal of NOR as compared with that of OFL was attributed to a high steric hindrance of OFL due to its bulky structure. The adsorption kinetic data for both the antibiotics followed the pseudo second order kinetics, and the sorption isotherm data was best described by the Langmuir model. Further, adsorption of the two antibiotics involved a combination of electrostatic interaction, anion exchange and hydrophobic interaction mechanisms. The FTIR spectrum of the modified LDH obtained before and after adsorption confirmed the adsorbate-adsorbent interaction. Finally, the microfiltration technique using a ceramic membrane was effectively employed to separate the loaded adsorbent from solution to recover and reuse the adsorbent with an aim to reduce the overall cost of the adsorption process. [Display omitted] •Hybrid adsorption cum membrane microfiltration introduced for antibiotics removal•SDS modified Ni-Al LDH contributed as an adsorbent to wastewater treatment.•Low cost microfiltration membrane applied to reduce the overall operation cost•Modified LDH is better for adsorption of NOR (98.7%) and OFL (94.6%).•Established scheme can be employed efficient removal of fluoroquinolone antibiotics.